Adverse pregnancy outcomes are associated with lower cut-offs for maternal hyperglycemia in Malaysian women: a retrospective cohort study - Yong, Heng Yaw; Mohd Shariff, Zalilah; Rejali, Zulida; Mohd Yusof, Barakatun Nisak; Bindels, Jacques; Tee, Yvonne Yee Siang; van der Beek, Eline M. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: This cohort aimed to determine glycemia distribution of pregnant women and maternal glycemia categories and its correlation with adverse pregnancy outcomes among Malaysian women. Methods: A retrospective cohort study of normal glycemia pregnant women. Binary logistic regression was used to examine the associations between maternal glycemia categories and adverse outcomes. Results: Women with elevated fasting plasma glucose (FPG) were at lower risk of having SGA infants (aORFPG 4= 0.64, 95% CI= 0.47 – 0.85; aORFPG 6= 0.68, 95% CI= 0.43– 0.98; aORFPG 7= 0.64, 95% CI= 0.42–0.96) than those women in category 1. Women in the higher 2-hour plasma glucose (2hPG) category had a nearly two-fold risk of having LBW and LGA infants. Hyperglycemia less severe than gestational diabetes mellitus (GDM) was associated with LGA (aOR= 1.22, 95% CI= 1.07 – 1.88) and caesarean delivery (aOR= 1.80, 95% CI= 1.20 – 2.69), in the meanwhile GDM was associated with caesarean delivery (aOR= 1.33, 95% CI= 1.02 –1.79). Conclusion: Cut-off points for FPG and 2hPG that relate to adverse pregnancy outcomes started at 4.9 – 5.0 mmol/l and 7.5 – 7.7 mmol/l. These cut-off points were lower than the current recommended criteria of Clinical Practice Guideline (CPG) of Malaysia for GDM diagnosis. Large-scale studies are required to identify the optimal GDM cut-off.